Report of the Committee on Finance relative to the sale of the state's investments in internal improvements for the redemption of the public debt : October 2, 1863 (Document (Virginia. General Assembly. Senate) ;, 1863)
October 2, 1863 Report of the Committee on Finance as to whether the state should sell its investments in the internal improvement companies in for the redemption of public debt, per the governor's message. After consideration, the committee determined that this would not be appropriate.